Research hotspots and frontiers in non-specific low back pain: a bibliometric analysis - Mao, Qiangjian; Wang, Yuqing; Xu, Shiqi; Wu, Desheng; Huang, Guomin; Li, Ziru; Jiao, Lin; Chi, Zhenhai (Frontiers in Neurology, 2024)
BackgroundExtensive research has been conducted worldwide on non-specific low back pain (NSLBP), some researchers published a bibliometric analysis of NSLBP in 2020, but there have been no supplements or updates since then. Therefore, this study aimed to analyze the research hotspots and frontiers in NSLBP over the last decade.MethodsPrimary sources on NSLBP were obtained from the Web of Science Core Collection database from 2014 to 2023. CiteSpace V6.2. R7 (64-bit) and VOSviewer 1.6.19 software were used to analyze the number and centrality of journals, countries, institutions, authors, references, and keywords, and the functions of co-occurrence and clustering were applied to draw a visual knowledge map.ResultsIn the past decade, the annual publication volume of studies on NSLBP has shown an overall upward trend year by year, with obvious temporal stages and great development potential. In total, 2,103 articles contained six types of literature, with the highest proportion being original research articles (1,633 articles, 77.65%), published in 200 journals. BMC Musculoskeletal Discourses (90 articles, 4.28%) had the highest number of publications, and the British Medical Journal had the highest impact factor (105.7). Furthermore, the United States of America (329 articles, 15.64%) had the highest publication volume, the University of Sydney (139 articles, 6.61%) was the research institution with the highest production, Maher, Chris G (36 articles, 1.71%) was the author with the most published articles, and Hoy, D (571 articles, 27.15%) was the most frequently cited author. The most cited of articles is “Non-specific low back pain” published in the LANCET, with 1,256 citations.ConclusionThis article summarizes the current research status of NSLBP and predicts future research hotspots and frontiers. In recent years, adolescents have become a high-risk group for NSLBP. Pain neuroscience education, motor control, spinal manipulative therapy, and acupuncture are effective means to treat NSLBP. Biomechanics and trunk muscles as entry points are effective ideas for the treatment of NSLBP pain. Furthermore, anxiety, neck pain, non-specific musculoskeletal pain, fibromyalgia, and musculoskeletal disorders are diseases that are closely related to NSLBP. In the future, attention should be paid to the design of research plans, increasing the research intensity of randomized controlled trials, strengthening follow-up, and the timely updating of guidelines, which will result in higher quality and high-level scientific evidence for research on NSLBP.